RESEARCH OF THE CHEMICAL COMPOSITION OF QUAIL MEAT WHEN ADDING A MINERAL FEED ADDITIVE TO THEIR DIET - Montayeva, N. S.; Abdrakhmanova, D. A.; Svotina, M. A.; Nurzhanova, F. Kh. (Ғылым және білім=Наука и образование=Science and education № 3-1 (68), 2022)
The article shows studies of the analysis of the chemical composition of quail meat when a mineral feed additive is added to the diet. The relevance of the work is associated with two important conditions. Firstly, it is closely related to the development of a new mineral feed additive based on the opoka rock obtained from the Taskalinsky deposit of the West Kazakhstan region. Secondly, the cultivation of healthy and productive poultry in order to ensure the food security of our country is one of the main objectives of our experiment. Conducted meat studies to assess the indicators of the chemical composition in order to use the feed additive on experimental poultry (quails) made it possible to obtain the following results: their total amount is 100. Moisture in all samples was no more than 72.0, dry matter - no more than 21.0, protein - no more than 4.0, fat - no more than 3.9, ash - no more than 0.7. Thus, a comprehensive analysis of the results obtained on the basis of scientific and experimental studies of the chemical composition of meat to assess the indicators revealed the harmlessness of mineral feed additives when used in the diet of quails, as well as an improvement in the general condition of birds.В статье представлены результаты анализа химического состава мяса перепелов при добавлении в их рацион кормовой добавки. Актуальность исследования связана с двумя важными факторами. Во-первых, тесно связана с разработкой новой минеральной кормовой добавки на основе породы опока, полученной из Таскалинского месторождения Западно- Казахстанской области. Во-вторых, выращивание здоровых и высокопродуктивных птиц в целях обеспечения продовольственной безопасности Республики Казахстан является одной из главных задач нашего эксперимента. Проведенные исследования мяса для оценки показателей сухого вещества, влаги, жира, золы и белка с целью применения минеральной кормовой добавки на подопытных птицах (перепелах) позволили получить следующие результаты: их общая сумма равна 100. Влага во всех образцах составила не более 72,0, сухое вещество – не более 21,0, белок – не более 4,0, жир – не более 3,9, зола – не более – 0,7. Таким образом, комплексный анализ результатов, полученных на основе научных и экспериментальных исследований химического состава мяса для оценки показателей выявил безвредность минеральной кормовой добавки при использовании в рационе перепелов, а также улучшение общего состояния птиц
Keywords: отечественное издание; научный журнал; периодическое издание; журнал коксон; ринц; dry matter; перепелки; кормление перепелок; мясо перепелки; мясо птицы; кормовые добавки; кормление птиц; moisture, protein; fat; ash